BIMBINGAN TEKNIS PAJAK PENGHASILAN BADAN PADA JASA LAYANAN KESEHATAN DI KOTA KENDARI - Ramadhan, Andi Muhammad Fuad; Hasbudin, Hasbudin; Dali, Nasrullah; Safaruddin, Safaruddin; Fitriaman, Fitriaman; Purnaman, Si Made Ngurah; Pebrianti, Vina Olivia; Syaiah, Syaiah; Hasnidar, Hasnidar; Adam, Baqir Muh. (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This community service activity is conducted with the aim of providing knowledge and understanding to the management of Healthcare Service Providers in Kendari, particularly employees involved in preparing financial statements and tax reports, regarding Corporate Income Tax. The strategic target of this activity is the management of Healthcare Service Providers in Kendari, especially employees responsible for preparing tax reports and those tasked with withholding or collecting Corporate Income Tax. The method used in this outreach activity is a persuasive-educative approach, which involves providing theoretical explanations accompanied by practical examples from similar business entities, followed by discussions and a Q&A session to assess understanding of the Withholding and Reporting of Corporate Income Tax. The results of this community service show that by using a persuasive-educative approach combined with practical simulations, the activity not only expanded participants' knowledge of tax regulations but also strengthened their ability to independently apply the Coretax Administration System-based electronic reporting system. Overall, the activity was successfully implemented and achieved its main objective, which was to enhance tax compliance and the financial governance of healthcare service institutions.